Alimentos fuentes de sodio: análisis basado en una encuesta nacional en Colombia (2015)
ABSTRACT: A high sodium intake is an independent risk factor for Cardiovascular diseases –CVD–. Thus, a strategy to reduce blood pressure and CVD risk throughout reducing sodium intake is promoted worldwide. In order to design an adequate strategy, it is important to identify the main sources of sodium in food, which has been evaluated mainly in developed countries. Objectives: to identify foods that provide sodium in Colombians diet, based on data from the National Nutritional Survey –ENSIN–. Furthermore, to determine sodium amount intake from foods. Methods: data obtained by 24 hours recall (R24h) from 39 413 apparently healthy, non-pregnant population between 2-64 y old population were analyzed. Food groups source of sodium and sodium were determined. Results: 1 274 food were reported by R24h. 95 foods contributed with 72% of total sodium from foods and were divided into 12 groups. The mayor sodium source in the diet was bakery products (30.5%). Average and median sodium intake without salt addition were: 816.4 ± 474.1 and 721.0 mg/d variable (RQ = 476.0 to 1051.0)mg/d, respectively. Sodium intake from food was higher in men (784.0 mg/d; RQ = 511.0 to 1156.0) than in females (665.0 mg/d; RQ = 448.0 to 953.0); p < 0.001. Conclusion: the present study identified the main sources of sodium in Colombians diet. Based on this analysis it is important to prioritize strategies in some groups, especially bakery products. It is also necessary to consider geographical area to implement a relevant strategy.